Association between the prevalence of obstructive sleep apnoea and the severity of keratoconus. Issue 12 (2nd July 2015) - Naderan, Mohammad; Rezagholizadeh, Farzaneh; Zolfaghari, Masoome; Naderan, Morteza; Rajabi, Mohammad Taher; Kamaleddin, Mohammad Amin
Abstract : Aim: The purpose of this study was to determine the association between prevalence of obstructive sleep apnoea (OSA) in patients with keratoconus (KC) and the severity of KC. Methods: Six-hundred and sixteen patients with KC and 616 patients without KC in the control group were enrolled in this prospective case–control study. Both groups were matched by age, gender, and body mass index (BMI). The Berlin Questionnaire was administered in both groups. Keratometric and topographic measurements of the KC eyes were recorded. Results: Seventy-six (12.3%) and 40 (6.5%) patients were identified as high risk for developing OSA in KC and control groups, respectively (p<0.001). Family history of OSA and BMI were the risk factors for OSA in the KC group, while in the control group the only risk factor for OSA was the patient's gender. Patients with KC with a high risk of OSA had a significantly higher mean K, flat K, steep K (p<0.05), and a thinner corneal thickness (p<0.05). The severity of KC decreased in both OSA groups except for the grade 4 of high risk group which was the second most frequent group after grade 1 (p=0.005). Conclusions: Our study revealed that patients with KC are at increased risk of developing OSA, and patients with KC who are at higher risk of developing OSA may have more severe KC.